Antimicrobial polymers : from theoretical studies to real-life applications - Hou, Zheng (Nanyang Technological University, 2020)
Developing antibiotic agents against multidrug resistance bacteria is considered as an urgent and important healthcare challenge. Many cationic antimicrobial peptides (AMPs) or polymers have been developed to overcome resistance, but it is difficult to balance the mammalian cell compatibility and bactericidal efficacy because most cationic AMPs or polymers are based on cationic and hydrophobic components which also interrupt mammalian cell membrane. In this thesis, based on natural chitosan, the cationic peptidopolysaccharide (CSM5-K5) and polysaccharide (2,6-DAC) without hydrophobic components were synthesized with excellent antimicrobial efficacy and mammalian cell compatibility. The short peptidopolysaccharide chitosan-graft-oligolysine (CSM5-K5) has excellent antimicrobial activity measured by MIC values ranging from 16 to 64 μg/mL against broad spectrum of Gram-positive and Gram-negative bacteria including Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Pseudomonas aeruginosa and Salmonella. CSM5-K5 also have excellent in vitro compatibility towards mammalian cells. The in vivo tests demonstrated that CSM5-K5 can reduce the load of Methicillin-resistant Staphylococcus aureus (MRSA) by 3.3log10 orders in a murine wound model. The antimicrobial mechanism of cationic peptidopolysaccharide was also studied and compared with linear cationic polylysine (K100). The 2,6-DAC also shows excellent and broad intrinsic antimicrobial efficacy against Staphylococcus aureus, Listeria, E. coli, Pseudomonas aeruginosa and A. baumannii (MIC from 8-32 μg/mL) and excellent compatibility towards mammalian cells. Moreover, the 2,6-DAC shows synergism with various antibiotics including protein synthesis inhibitor (Tobramycin), DNA gyrase inhibitor (Novobiocin) and β-lactamase inhibitor (Tazobactam). The in vivo study shows 2,6-DAC combined with antibiotics can achieve 2log10 orders inhibition of A. baumannii in murine intraperitoneal infection model and lung infection model. To further reduce the possible bacterial infection caused by contamination on surface of medical device such as catheter, a novel coating strategy of catheter (H(N)-b-S) was developed with excellent and broad spectrum antibiofilm efficacy. The modified catheter can inhibit >4log10 orders of bacterial contamination in both in vivo and in vitro studies for 24 hrs against all pathogens tested (Enterococcus, S. aureus, K. pneumonia, A. baumannii, P. aeruginosa, E. coli, and Candida). The modified catheter also has good compatibility with blood immune cells and mammalian cells. The potential ability for large scale manufacture of such coated catheter was proved by coating of 30cm long commercially available polyurethane catheter successfully and achieving 3log10 inhibition of P. aeruginosa and S. aureus biofilm formation for 30 days. The findings reported in this thesis provide a package of solutions to prevent and treat bacteria/fungus infections.